Hubungan Metakognisi dengan Indeks Prestasi Kumulatif (IPK) Pada Mahasiswa Program Studi Pendidikan Dokter - Silalahi, Agnes M.; Pangemanan, Damajanty H. C.; Angmalisang , Elvin C. (Universitas Sam Ratulangi, 2025)
Abstract: Grade Point Average (GPA) is an evaluation parameter of student learning outcomes at university, and can be influenced by many factors, one of which is metacognition. Metacognition helps a person become lifelong learners who are independent in learning and able to adapt to the development of science. This study aimed to determine the relationship between metacognition and GPA of medical students of batch 2022 in Universitas Sam Ratulangi. This was a quantitative study with an observational and analytical approach, and designed with a cross-sectional model. Samples were medical students batch 2022 of Universitas Sam Ratulangi, as many as 211 students who met the inclusion criteria. Students' metacognition was measured using the Metacognitive Awareness Inventory (MAI) questionnaire, and GPA data obtained through the students’ transcripts. The results showed that respondents with very good metacognition (12.3%), good (34.1%), enough (52.6%), dan low (0,9%). Respondents’ GPA divided into praised (79,1%), very satisfactory (19,9%), satisfactory (0.5%), and unsatisfactory (0.5%). The Fisher’s Exact Test analysis obtained a p-value of 0.388 (p>0.05). In conclusion, there is not significant relationship between metacognition and GPA of medical students batch 2022 in Universitas Sam Ratulangi. Keywords: metacognition; grade point average; metacognitive awareness inventory Abstrak: Indeks Prestasi Kumulatif (IPK) merupakan suatu parameter evaluasi hasil belajar mahasiswa pada tingkat pendidikan tinggi, yang dapat dipengaruhi oleh banyak faktor, salah satunya ialah metakognisi. Metakognisi membantu seseorang menjadi lifelong learner yang mandiri dalam belajar dan mampu beradaptasi terhadap perkembangan ilmu pengetahuan. Penelitian ini bertujuan untuk mengetahui hubungan antara metakognisi dengan IPK pada mahasiswa angkatan 2022 Fakultas Kedokteran Universitas Sam Ratulangi. Jenis penelitian ialah kuantitatif dengan pendekatan observasional analitik, dan desain potong lintang. Sampel penelitian ialah mahasiswa angkatan 2022 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi berjumlah 211 orang yang memenuhi kriteria inklusi. Metakognisi mahasiswa diukur dengan menggunakan kuesioner Metacognitive Awareness Inventory (MAI) dan data IPK didapatkan melalui transkrip nilai mahasiswa. Hasil penelitian mendapatkan responden memiliki metakognisi sangat baik (12,3%), baik (34,1%), cukup (52,6%), dan rendah (0,9%). IPK responden terbagi menjadi pujian (79,1%), sangat memuaskan (19,9%), memuaskan (0,5%), dan kurang memuaskan (0,5%). Hasil analisis Fisher’s Exact Test mendapatkan nilai p=0,388 (p> 0,05). Simpulan penelitian ini ialah idak terdapat hubungan antara metakognisi dengan IPK pada mahasiswa angkatan 2022 Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sam Ratulangi. Kata kunci: metakognisi; indeks prestasi kumulatif; metacognitive awareness inventory